Students’ Experiences of EFL Assessment Using Wayground Paper Mode in a Rural Junior High School - Idris, Bayu Romli Idris; Yeny Prastiwi; Nur Hidayat (Samudra Publisher, 2026)
The digital divide remains a critical barrier to equitable access to technology-based learning and assessment, particularly in rural educational settings. While previous studies have explored the use of Wayground and other gamified platforms in urban schools with adequate digital infrastructure, limited research has examined students’ experiences with Wayground Paper Mode in contexts where online tools are inaccessible. This study aims to explore students’ emotional and psychological experiences during the implementation of Wayground Paper Mode in English as a Foreign Language (EFL) assessments, and to investigate how the digital divide influences their engagement, learning challenges in a rural junior high school in Indonesia. Employing a qualitative phenomenological research design, data were collected from 18 Grade 9 students through semi-structured interviews, classroom observations, and reflection journals, complemented by teacher interviews for triangulation. Thematic analysis revealed four major themes: (1) emotional and psychological responses to offline assessments, (2) challenges arising from digital inaccessibility, (3) enhanced engagement through gamified paper-based activities, and (4) perceptions of learning effectiveness. The findings indicate that Wayground Paper Mode serves as an engaging, low-tech alternative that helps bridge the digital gap while maintaining the motivational benefits of gamification. However, challenges such as instructional clarity and consistency of facilitation remain significant. The study underscores the need to adapt gamified assessment tools for rural EFL contexts to foster more inclusive and equitable learning opportunities in resource-limited environments.